(untitled) (Nuntius Antiquus, 2025)
Until the middle of the last century, a significant portion of historiography considered Diodorus a mere copyist, and his value as a source lies primarly in the works that he supposedly used. However, this was not always the case. The author of Agyrium was praised and quoted for many centuries, especially by the early Christians and the Byzantines. His autonomy and uniqueness were rediscovered in the 1950s, and today they set the tone for studies on Diodorus. This article seeks to analyze the evolution and changes of Diodorian studies over the centuries, in order to understand what is the current stage of academic discussions.